Acute Promyelocytic Leukaemia: An Experience with 6 Cases - Kabir, MD Alamgir; Rahman, MD Mujibur; Mogni Mowla, Syed Ghulam; Moniruzzaman, MD; Rahim, Abdur; Jahan, Sharmin; Ahsan, HM Nazmul (Journal of Medicine, 2011)
Background and objective: Acute promyelocytic leukaemia (APL) is considered a distinct entity among the acute myeloid leukemias (AML). Our purpose is to see its clinical presentations and outcome with ATRA (all- trans retinoic acid). Materials and methods: It is a retrospective descriptive study of 6 patients diagnosed by cytologic criteria between November 2008 and February 2011 in two tertiary care hospitals in Dhaka, Bangladesh. All specific information were recorded in standardized data sheet and analyzed manually. Results: Mean (SD) age of patients was 28.6 (±7.84) years with equal gender distribution. Fever >101°F, weakness, easy fatigability, and bleeding manifestations were common presentations (100%). The other manifestations were bony tenderness, purpuric spots or DIC, but no lymphadenopathy and organomegaly were seen. Mean (±SD) Hb was 9.03 (±1.06) gm/dl, in 66% ESR was >50mm in 1st hr with 50% leukocytosis and 50% leucopenia but 100% thrombocytopenia.In the peripheral blood 40%-85% of the leukocytes were blast cells. Bone marrow was done in all cases which suggested AML-M3 (Acute promyelocytic leukemia) and cytogenetic diagnosis were done in 3 cases, which showed t(15;17)PML-RARA fusion protein positive. ATRA (all-trans retinoic acid) plus chemotherapy (daunorubicin ± cytarabine) achieved complete remission in 5 (80%) patients. Conclusion: Modern treatment is highly effective if administered early. Keyword: Acute promyelocytic leukaemia, PML/RARA fusion protein, All- trans retinoic acid (ATRA). DOI: http://dx.doi.org/10.3329/jom.v12i2.8420 JOM 2011; 12(2): 139-141